Mycorrhization level in truffle plants and presence of concurrent fungi - Leonardo B. Falini (Acta Mycologica, 2013)
In Italy, to improve good practices for truffle cultivation, some regional governments require specific certification of mycorrhization level and plant quality for marketing, out-planting and establishment of truffle orchards. The Department of Applied Biology at the University of Perugia has dealt with certification of truffle plants since the 1980’s. Here we show the mycorrhization analysis of different host species previously inoculated with truffle spores by an Italian commercial nursery.